"At the mercy of some of the regulations": the impact of the residency match and return of service requirement on the early-career decisions of international medical graduates in Canada - Mathews, Maria (2022)
Background: Return-of-service (ROS) agreements require international medical graduates (IMGs) who accept medical residency positions in Canada to practice in specified geographic areas following completion of training. However, few studies have examined how ROS agreements influence career decisions. We examined IMG resident and early-career family physicians’ perceptions of the residency matching process, ROS requirements, and how these factors shaped their early career decisions. Methods: As part of a larger project, we conducted semi-structured qualitative interviews with early-career family physicians and family medicine residents in British Columbia, Ontario and Nova Scotia. We asked participants about their actual or intended practice characteristics (e.g., payment model, practice location) and factors shaping actual or intended practice (e.g., personal/professional influences, training experiences, policy environments). Interviews were transcribed verbatim and a thematic analysis approach was employed to identify recurring patterns and themes. Results: For this study, we examined interview data from nine residents and 15 early-career physicians with ROS agreements. We identified three themes: IMGs strategically chose family medicine to increase the likelihood of obtaining a residency position; ROS agreements limited career choices; and ROS agreements delayed preferred practice choice (e.g., scope of practice and location) of an IMGs’ early-career practice. Conclusions: The obligatory nature of ROS agreements influences IMG early-career choices, as they necessitate strategically tailoring practice intentions towards available residency positions. Existing analyses of IMGs’ early-career practice choices neglect to distinguish between ROS and practice choices made independently of ROS requirements. Further research is needed to understand how ROS influences longer term practice patterns of IMGs in Canada.